KEBERADAAN MAHKAMAH KONSTITUSI DI INDONESIA DALAM PERANNYA MENJAGA HAK ASASI MANUSIA DAN HAK KONSTITUSIONAL WARGA NEGARA (SUATU PERWUJUDAN NYATA) - Francois Geny Ritonga (Honeste Vivere, 2023)
The Constitutional Court is one of the judicial institutions in Indonesia, which was formed based on Article 24C of the 1945 Constitution and Law no. 24 of 2003 concerning the Constitutional Court. The powers of the Constitutional Court, such as: 1) Reviewing laws against the 1945 Constitution, 2) Deciding disputes over the authority of state institutions whose powers are granted by the 1945 Constitution, 3) Deciding the dissolution of political parties; and 4) Resolving disputes about the general election results. The purpose of writing is to see how far the authority of the Constitutional Court is applied in carrying out its functions and powers by using the normative juridical writing method. The findings prove that the Constitutional Court has carried out as stipulated in the 1945 Constitution and legislation and implemented a rule of law that recognizes and protects and guarantees the basic rights of citizens to the need for justice (access to justice) and equality before the law (equality before the law).